2019
DOI: 10.1001/jamanetworkopen.2019.4934
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Renin-Angiotensin System Inhibitors With Prevention of Postoperative Atrial Fibrillation and Adverse Events

Abstract: Key Points Question Does the use of renin-angiotensin system inhibitors have any association with reduction in atrial fibrillation and adverse events for patients undergoing cardiac surgery? Findings This systematic review and meta-analysis involving 11 unique studies with 27 885 patients undergoing cardiac surgery found no additional association between preoperative renin-angiotensin system inhibitor therapy and a reduced risk of postoperative atrial fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Our study showed that patients with POAF were elder, had a higher prevalence of CKD, higher CHA2DS2-VASc score, and poorer echocardiographic profile, all of which are compatible with previous studies (23)(24)(25)(26). Also noted, patients in POAF group were less frequently taking ACEI/ARBs and beta-blockers, both medications were proved to be able to prevent the development of POAF (27,28).…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that patients with POAF were elder, had a higher prevalence of CKD, higher CHA2DS2-VASc score, and poorer echocardiographic profile, all of which are compatible with previous studies (23)(24)(25)(26). Also noted, patients in POAF group were less frequently taking ACEI/ARBs and beta-blockers, both medications were proved to be able to prevent the development of POAF (27,28).…”
Section: Discussionsupporting
confidence: 90%
“…In animal and in vitro studies, the inhibition of the RAAS impairs plaque development and suppress atherosclerosis ( 31 ). Additionally, ASi may also reduce the risk of rhythm disturbances e.g., atrial fibrillation ( 32 ). Moreover, the prophylactic use of ASi as a prevention of CV complications showed promise in several cancer types e.g., before anthracycline treatment for breast cancer ( 33 ), among lymphoma ( 34 ), kidney ( 35 ), or pancreatic cancer patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…790 Perioperative steroid use, renin-angiotensin system inhibitors, digoxin prophylaxis, calcium antagonist prophylaxis, n-3 polyunsaturated fatty acids, glucose-insulinpotassium therapy, vasopressin, and NSAIDs have been shown to lack promise. 771,[791][792][793][794][795][796] Intraoperative injection of botulinum toxin into epicardial neural ganglia has been shown to be promising in small RCTs with a larger study in progress. 797…”
Section: Other Potential Therapiesmentioning
confidence: 99%